"No former travellers having attained such a height on the Earth's surface": Instruments, inscriptions, and bodies in the Himalaya, 1800–1830. (March 2018) - Fleetwood, Lachlan
East India Company surveyors began gaining access to the high Himalaya in the 1810s, at a time when the mountains were taking on increasing political significance as the northern borderlands of British India. Though never as idiosyncratic as surveyors insisted, these were spaces in which instruments, fieldbook inscriptions, and bodies were all highly prone to failure. The ways surveyors managed these failures (both rhetorically and in practice) demonstrate the social performances required to establish credible knowledge in a world in which the senses were scrambled. The resulting tensions reveal an ongoing disconnect in understanding between those displaced not only from London, but also from Calcutta, something insufficiently emphasized in previous histories of colonial science. By focusing on the early nineteenth century, often overlooked in favor of the later period, this article shows the extent to which the scientific, imaginative, and political constitution of the Himalaya was haphazard and contested.